The new insertion of urban agriculture in the production of the city - Nagib, Gustavo [UNESP] (Univ Lille I Sci & Tech, 2024)
Urban agriculture (UA) is being incorporated into the process of production of the city. In certain eco-districts, developers allow associations, startups and solidarity economy initiatives to partially occupy the site during the construction phase. In this context, ephemeral UA initiatives are recurring in Paris, awarding construction sites new signification, both economy- and usage wise. This article addresses this theme following research conducted between 2018 and 2021 in Greater Paris, where UA has integrated as a model of edible landscaping, educational vegetable gardening or urban farming. In this temporary use areas, the consumption of space ensures the continued use of the urban tissue while these eco-districts are also subject to changes and improvisations thanks to a broader variety of practices and initiatives that adapt to spatial changes according to the pace of the construction works and can become permanently integral to the future eco-districts. Qualitative in nature, the research relied on fieldwork, systematic field observation, participation in events held within the initiatives being studied, and bibliographic review, including the analysis of documents of the projects investigated. The findings indicate that temporary occupations become incubators for new UA initiatives and stimulate the emergence of associations and companies, allowing them a first contact with the public and a first opportunity to test their services. Moreover, UA also integrates into a new urbanism that anticipates the presence of different kinds of agricultural practices in urban areas in the long term, bringing together various players, such as developers, associations, startups, dwellers and public sector, thus creating what we identify as a hybrid mix of UA practices.
Keywords: urban agriculture; production of the city; eco-district; temporary use; Paris